(Liquid + liquid) equilibria for (water + 1-propanol + diisopropyl ether + octane, or methylbenzene, or heptane) systems at T = 298.15 K. (August 2015) - Zhou, Xiaoming; Chen, Yao; Wang, Cui; Guo, Jitai; Wen, Caiyu
Highlights: DIPE is one of the most ideal additives for its obvious advantages. Good agreements between the experimental and correlated tie-lines. Correlated results are better by using the modified UNIQUAC model. DIPE and 1-propanol are more soluble with hydrocarbon compounds. Abstract: (Liquid + liquid) equilibria (LLE) data were presented for one ternary system of {water + octane + diisopropyl ether (DIPE)} and three quaternary systems of (water + 1-propanol + DIPE + octane, or methylbenzene, or heptane) at T  = 298.15 K and p  = 100 kPa. The experimental LLE data were correlated with the modified and extended UNIQUAC models. Distribution coefficients were derived from the experimental LLE data to evaluate the solubility behavior of components in organic and aqueous phases.